Identification of Environmental-Based Health Problems in Coastal Area of Mata Public Health Centre - Hariati Lestari (Miracle Journal of Public Health, 2022)
Health problems caused by environmental conditions around humans in the form of sewerage, garbage disposal, water sources and family latrines. The purpose of this study was to identify environmental-based health problems in the working area of the Mata Health Center. This type of research is a quantitative descriptive research with a survey approach. The population in this study is the entire community, totaling 11,298 people. The sample in this study was 200 respondents with a sampling technique using simple random sampling. The results showed that the environmental-based diseases in the coastal areas of the Mata health center were diarrhea (58%), dengue (12%), malaria (4.5%), ARI (5.5%), contact dermatitis (20%), While the description of environmental factors in the coastal area is that the majority of clean water sources come from PDAM (60%), the condition of the water used is in the smelly category (1%), tasted water (7.5%), colored water (8.5% ); there are still those who do not have latrines (8%), latrines are not always closed (42.5%), do not clean latrines (7%); there are still those who do not have a garbage disposal at home (4%), and even if they have a garbage can, there are still non-watertight and closed garbage disposal containers (28%).The conclusion of this research is that there were still environmental factors that did not meet health requirements in the coastal area of ​​the Mata Health Center and caused environmental-based diseases.